Palladium-catalysed cyclisation of ynamides and propargyl tethered iodosulfonamides with boronic acids leading to benzosultams. Issue 31 (29th July 2021) - Sandeep, K.; Siva Reddy, Alla; Kumara Swamy, K. C.
Abstract : A convenient route to benzo[ d ]isothiazole and benzo[ e ][1, 2]thiazine scaffolds using ynamides and arylboronic acids under [Pd]-catalysis is reported; the synthetic utility has been demonstrated by a gram-scale synthesis. Abstract : An efficient and straightforward Pd-catalysed synthesis of diversely substituted sultams utilising ynamides and boronic acids is disclosed; toluene was found to be the most suitable solvent for this transformation. This strategy has been successfully applied to generate dihydrobenzo[ d ]isothiazole 1, 1-dioxides and dihydro-2 H -benzo[ e ][1, 2]thiazine 1, 1-dioxides. The advantages of this protocol are good functional group tolerance, broad substrate scope, high-yielding reaction and low catalyst loading to access benzofused sultams with five-/six-membered rings. The synthetic utility has been demonstrated by a gram-scale synthesis. A plausible catalytic cycle involving carbopalladation has been proposed for this transformation.